IMPLEMENTASI PEMBELAJARAN MENDALAM BERBASIS DIGITAL TERHADAP SPATIAL THINKING SISWA PADA MATA PELAJARAN GEOGRAFI FASE E DI SMAN 1 LUHAK NAN DUO - Agnesia Tamba; Bayu Wijayanto; Ernawati; Anisa Yudita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation and effectiveness of digital-based deep learning on students' spatial thinking skills in Geography Phase E at SMAN 1 Luhak Nan Duo. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The study sample consisted of 29 students from class XE1 as the experimental class and 28 students from class XE2 as the control class. Data collection was carried out through spatial thinking tests in the form of pretests and posttests, as well as student response questionnaires. The digital media used included Zoom Earth, Windy, and AccuWeather. The results of the study indicate that the implementation of digital-based deep learning was successful through mindful, meaningful, and joyful learning activities utilizing digital media to explore atmospheric phenomena.